2014
DOI: 10.1128/aem.01697-14
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Gene Expression in Diverse Cyanobacterial Species by Using Theophylline-Responsive Riboswitches

Abstract: Cyanobacteria are photosynthetic bacteria that are currently being developed as biological production platforms. They derive energy from light and carbon from atmospheric carbon dioxide, and some species can fix atmospheric nitrogen. One advantage of developing cyanobacteria for renewable production of biofuels and other biological products is that they are amenable to genetic manipulation, facilitating bioengineering and synthetic biology. To expand the currently available genetic toolkit, we have demonstrate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
117
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 117 publications
(122 citation statements)
references
References 44 publications
3
117
1
Order By: Relevance
“…It extends previous work on the applicability of this riboswitch in cyanobacteria (Ma et al, 2014;Nakahira et al, 2013). In addition, our data imply an issue about this system: the effect of the sequence around the riboswitch.…”
Section: Expression Level Control By Theophylline Concentrationsupporting
confidence: 89%
See 1 more Smart Citation
“…It extends previous work on the applicability of this riboswitch in cyanobacteria (Ma et al, 2014;Nakahira et al, 2013). In addition, our data imply an issue about this system: the effect of the sequence around the riboswitch.…”
Section: Expression Level Control By Theophylline Concentrationsupporting
confidence: 89%
“…PCC 7120, Leptolyngbya sp. BL0902 and Synechocystis WHSyn (Ma et al, 2014;Nakahira et al, 2013). Here, we describe the construction of a conjugative expression vector using a theophylline-responsive riboswitch and examine the resulting expression levels and its regulation using a green fluorescence protein (GFP) reporter in Synechocystis.…”
Section: Figmentioning
confidence: 99%
“…Therefore, we used riboswitches B and C, which have high induction ratios but very low levels of basal expression in the absence of theophylline. 21 …”
Section: Resultsmentioning
confidence: 99%
“…19 A set of synthetic theophylline-responsive riboswitches that control translation, originally developed and evaluated in eight different bacterial species by Topp et al, 18 have since been shown to provide robust control of gene expression in several phylogenetically diverse cyanobacteria. 2021 …”
Section: Introductionmentioning
confidence: 99%
“…high-light-responsive p sbA promoter, copper-regulated p etE promoter, nitrate/nitrite-inducible P nirA promoter and the nickel-regulated nrsA promoter) have been assessed in cyanobacteria, induction of these regulatory systems could concurrently affect the endogenous cognate regulon and result in unwanted effects [1, 31, 32]. To evaluate appropriate promoters useful for driving CRISPRi in PCC 7942, we compared different inducible promoters (P smt , P LtetO1 , P ConII-ribo , P trc , P LlacO1 and P BAD ) derived from E. coli or cyanobacteria (Additional file 1: Figure S5).…”
Section: Resultsmentioning
confidence: 99%